The Impact of Digital Communication on UMSU Student in Game Online - Hidayat, Fadhil Pahlevi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to find out the impact of digital communication on UMSU students in playing online games. The online game that is the focus of the research is Mobile Legend, because Mobile Legend is the most popular online game in Asia, especially in Indonesia with several users of up to 50 million active users. The research method is descriptive qualitative with research informants who are UMSU students who actively play mobile legends using observation, interviews, and documentation as data collection techniques, as well as data analysis techniques using data reduction, data presentation, and conclusion verification. The research results show that there are negative and positive impacts from UMSU students' digital communication in playing mobile legend online games. The negative impact is that students become more emotional easily it carries over into everyday life, and the positive impact is that students make new friends even outside the city and province. So, to anticipate the negative impacts of digital communication, students are expected to have media literacy skills